Chemical Experiments with Cigarettes (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Studies on the study of metabolic processes in the body, in particular, the determination of the ability to accumulate toxic and potentially toxic elements in the body of animals exposed to nicotine were carried out in 2 stages, while at each stage the experimental animals were divided into two groups of 30 heads each (one control and one experimental group).The experimental animals were exposed to tobacco smoke for 30 minutes in the seed chamber. The control group consisted of intact animals, daily stay for 30 minutes in a seed chamber with no tobacco smoke.A plastic chamber with a volume of 0.3 m was used to simulate "passive smoking". The smoke of the chamber was carried out by burning cigarettes in a special holding device. As the cigarette burned, they were replaced, thereby ensuring a constant flow of smoke into the priming chamber. An even distribution of smoke was provided by a fan.